Exploring Relationships among Social Norms, Aesthetics, and HOA Regulations and Water Conservation - Amanda D. Ali; Laura A. Sanagorski Warner (EDIS, 2019)
In the United States, landscape irrigation often consumes 50% or more of residential water used, and aesthetics may take preference over water-conserving elements in the landscape. Other factors such as perceived social norms and homeowners' association (HOA) regulations also impact water conservation behaviors. Binary logistic regression estimated the impact of aesthetics, perceived social norms, and HOA regulations on water conservation intentions. Findings revealed that when individuals placed a higher-than-average value on aesthetics and perceived stronger social support for conservation, home irrigation users had greater intent to conserve water. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Amanda D. Ali and Laura A. Sanagorski Warner. http://edis.ifas.ufl.edu/wc331